Handbook of optical sensors - Santos, José Luís; Farahi, Faramarz; Abolbashari, Mehrdad (CRC Press, 2015)
Handbook of Optical Sensors provides a comprehensive and integrated view of optical sensors, addressing the fundamentals, structures, technologies, applications, and future perspectives. Featuring chapters authored by recognized experts and major contributors to the field, this essential reference: Explains the basic aspects of optical sensors and the principles of optical metrology, presenting a brief historical review; Explores the role of optical waveguides in sensing and discusses sensor technologies based on intensity and phase modulation, fluorescence, and plasmonic waves; Describes wavefront sensing, multiphoton microscopy, and imaging based on optical coherence tomography; Covers optical fiber sensing, from light guiding in standard and microstructured optical fibers to sensor multiplexing, distributed sensing, and fiber Bragg grating; Offers a broad perspective of the field and identifies trends that could shape the future, such as metamaterials and entangled quantum states of light.